2023
DOI: 10.1111/1460-6984.12931
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions for echolalia in autistic children

Catherine Blackburn,
Martina Tueres,
Niki Sandanayake
et al.

Abstract: IntroductionEcholalia, the repetition of others’ speech, is a common observation in autistic people. Research has established that echolalia is functional and meaningful for many; however, some clinicians and researchers continue to characterise it as pathological and in need of reduction. The aim of this systematic review was to understand the range and impact of interventions for echolalia in autistic children.MethodA systematic search was conducted according to the Preferred Reporting Items for Systematic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
2
0
1
Order By: Relevance
“…Se ocupa de las configuraciones del tracto vocal utilizadas para producir los sonidos del habla (fonética articulatoria), de las propiedades acústicas de los sonidos del habla (fonética acústica) y de la forma de combinar los sonidos para formar silabas, palabras y frases (fonética lingüística). (5) Lo antes expresado es conveniente analizar por todo logopeda puesto que se ha hecho referencia a la fonética/ fonología como uno de los componentes estructurales del lenguaje que no se pueden ver de forma aislada sino como una estrecha relación con el componente pragmático del lenguaje, puesto que la fonología y la fonética no son ciencias independientes, ambas se relacionan con el lenguaje, con sus componentes estructurales, (Fonética) ambas se encargan de ayudarnos a identificar porque los sonidos que salen de nuestras bocas son suaves o fuertes y porque cada idioma tiene propios códigos de comunicación (Fonología). (6,7) Las alteraciones fonéticas consisten en la incapacidad de producir (articular) correctamente los sonidos esperados a una determinada edad cronológica.…”
Section: Resultados Y Discusión Fonéticaunclassified
“…Se ocupa de las configuraciones del tracto vocal utilizadas para producir los sonidos del habla (fonética articulatoria), de las propiedades acústicas de los sonidos del habla (fonética acústica) y de la forma de combinar los sonidos para formar silabas, palabras y frases (fonética lingüística). (5) Lo antes expresado es conveniente analizar por todo logopeda puesto que se ha hecho referencia a la fonética/ fonología como uno de los componentes estructurales del lenguaje que no se pueden ver de forma aislada sino como una estrecha relación con el componente pragmático del lenguaje, puesto que la fonología y la fonética no son ciencias independientes, ambas se relacionan con el lenguaje, con sus componentes estructurales, (Fonética) ambas se encargan de ayudarnos a identificar porque los sonidos que salen de nuestras bocas son suaves o fuertes y porque cada idioma tiene propios códigos de comunicación (Fonología). (6,7) Las alteraciones fonéticas consisten en la incapacidad de producir (articular) correctamente los sonidos esperados a una determinada edad cronológica.…”
Section: Resultados Y Discusión Fonéticaunclassified
“…A majority of these were behaviourist approaches adopting strategies (e.g. differential reinforcement, tact training, redirection) to actively reduce echolalic utterances, with the explicit premise that gestalt language development is undesirable and interferes with 'normal' language development and social acceptance (Blackburn et al, 2023). More developmentally oriented approaches (e.g.…”
mentioning
confidence: 99%
“…The conceptual confusion around gestalt language, combined with neuro-normative frameworks that make assumptions around 'ideal' developmental trajectories and seek to erase autistic characteristics, has led to widespread pathologisation of gestalt language within clinical approaches targeting language development in autistic children. A recent systematic review (Blackburn et al, 2023) identified 15 studies of interventions aiming to reduce or eliminate echolalia. A majority of these were behaviourist approaches adopting strategies (e.g.…”
mentioning
confidence: 99%